Dampak Ketengangan Geopolitik terhadap Investasi Asing Langsung (FDI) di Indonesia - Zaza, Alfonsa Maria Satifa Umbu; Banoet, Rice Yohana; Dima, Enike Tje Yustin (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2025)
Global geopolitical tensions such as trade wars, military conflicts, and diplomatic rivalries have increasingly shaped the dynamics of foreign direct investment (FDI), creating uncertainty that disrupts investor confidence and reshapes global capital flows. This study aims to analyze how these geopolitical developments impact FDI inflows to Indonesia, a major emerging economy that aspires to become a high-income nation by 2045. Using a literature review approach supported by content analysis, this research synthesizes findings from academic journals, international economic reports, and policy documents published between 2019 and 2024. The results reveal that geopolitical tensions heighten investment risks, trigger capital flight, disrupt global supply chains, and cause currency depreciation, all of which negatively affect Indonesia’s investment climate. However, these global shifts also generate new opportunities. Indonesia may benefit from industrial relocation, particularly from multinational corporations seeking to diversify away from geopolitically sensitive regions. Additionally, Indonesia’s commitment to downstream industrialization and green economy development strengthens its investment appeal. To remain competitive, the country must accelerate structural reforms, improve human capital, and expand its digital infrastructure. Despite global uncertainty, Indonesia continues to maintain high FDI inflows, driven by relative political stability, large domestic market potential, and proactive government policy. This study contributes to a nuanced understanding of the risks and opportunities that geopolitical shifts present for emerging economies, especially in designing responsive investment strategies.